The development of interactive learning media based on articulate storyline 3 - Dahlan, Ahmad; Sriyanto, Sriyanto (JIPSINDO, 2024)
Utilizing technology in an effective and interactive learning process is driven by the development of science and technology. The teacher's contribution in learning activities as a facilitator and mediator provides facilities for ease of learning. Learning media based on Articulate Storyline 3 is one of the interactive multimedia options that can be used in the learning process. This type of development research is Research and Development (R&D). The development of learning media is carried out through ten steps in Research & Development (R & D) consisting of: 1) Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation, 5) Design Revision, 6) Trial Initial Product, 7) Product Revision, 8) End-Use Trial, 9) Final Product Revision and 10) Mass Production. Testing learning materials and media validation has met the very feasible category. This is evidenced by the results of the material expert validation of 90 with a percentage score of 85.71% and an average score of 4.29. The validation of media experts is equal to the percentage score of 87.86% and the average score is 4.39, indicating that the category group is very feasible. Initial product testing in small classes has validly met the attractiveness and effectiveness categories in use. This is evidenced by the total eligibility score by students from user data with a percentage of 83.08%. Based on the criteria in the eligibility table according to the Likert scale with a percentage of 83.08%, it is in the very feasible category. Testing the final product of developing interactive learning media based on Articulate Storyline 3 in large classes has been valid to meet the eligibility and effectiveness categories in use.